ANALISIS HUBUNGAN ANTARA BBLR DAN PREMATURITAS DENGAN IKTERUS NEONATORUM DI RSUD PROF. DR. MARGONO SOEKARJO PURWOKERTO - Ema Wahyuningrum; Erni Septiyani (Universitas Harapan Bangsa Purwokerto, 2013)
Background: Jaundice is also a symptom that is often found in newborns . The incidence ofjaundice in newborns ( BBL ) ranges from 50 % in term infants and 75 % in preterm infants .Survey data in hospitals Prof. Dr. Margono Soekarjo Purwokerto there are 614 cases ofjaundice in 2010 and in 2011 there was an increase to as many as 635 ( 15.7 % ) JaundiceNeonatorum . Objectives: To analysis the relationship between LBW and preamturitas againstjaundice Neonatorum in hospitals Prof. Dr. Margono Soekarjo in Methods: The study was adescriptive correlation method with retrospective approach, the population is 635 as neonatal,using sampling techniques quata sampling with a sample of 100 neonates, the instrument used isthe master table, and useful analysis of data using Chi Square .Results: No association was lbwto jaundice in the hospital Neonatorum Prof. Dr. Margono Soekarjo Purwoerto the value of p(Sig) 0.554. Prematurity No relation to neonatal jaundice in the hospital Prof. Dr. MargonoSoekarjo Purwokerto the value of p (Sig) 0.807. Conclusion: There was no association of LBWand prematurity in the hospital for jaundice Neonatorum Prof. Dr. Margono SoekarjoPurwokerto. Key words: : LBW, Prematurity and jaundice Neonatorum